Indoor wood combustion, carcinogenic exposure and esophageal cancer in southwest Kenya. (July 2021) - Mwachiro, Michael M.; Pritchett, Natalie; Calafat, Antonia M.; Parker, Robert K.; Lando, Justus O.; Murphy, Gwen; Chepkwony, Robert; Burgert, Stephen L.; Abnet, Christian C.; Topazian, Mark D.; White, Russell E; Dawsey, Sanford M.; et al.
Highlights: Biomarkers of smoke exposure (PAHs) were extremely high among Kenyan rural population. Women who cooked indoors with wood without adequate ventilation were particularly affected. This exposure was associated with the precursor lesion for esophageal cancer. Community-based efforts to improve ventilation and cooking practices are needed. Abstract: Background: Exposure to polycyclic aromatic hydrocarbons (PAHs) is a risk factor for esophageal squamous cell carcinoma (ESCC) in high-incidence areas of China, Iran and Brazil, but PAH assessments have not been conducted in East Africa, another ESCC hot spot. Objective: To evaluate demographic or lifestyle factors associated with the PAH biomarker concentrations in the study population, and whether PAH metabolite concentrations showed any associations with esophageal precancerous lesions. Methods: We recruited a community-based sample of 289 asymptomatic adults from a rural area of Kenya and performed Lugol's chromoendoscopy to detect esophageal squamous dysplasia (ESD); participants completed a questionnaire and provided a spot urine specimen. We analyzed urine for seven hydroxylated metabolites of naphthalene, fluorene, phenanthrene, and pyrene at the U.S. National Center for Environmental Health, and compared creatinine-corrected PAH metabolite concentrations with questionnaire data and the presence of ESD. Results: PAH metabolite concentrations among never tobacco users in these rural Kenya residents were 2.4–28.1 times higher than those reported from never tobacco users in Iran, Brazil and the USA. Female sex, cooking indoors, having no post-primary education, and age <50, but not tobacco use, were positively and significantly associated with PAH metabolite concentrations. Almost all participants used wood as cooking fuel. Nine participants had advanced ESD. Adjusted logistic regression showed a significant association between 2-hydroxynaphthalene (OR = 4.19, 95%CI: 1.01–17.47) and advanced ESD. All other PAH metabolites had positive but non-significant associations with advanced ESD. Conclusions: Urinary PAH metabolite concentrations among never tobacco users are markedly higher in this group from Kenya than in other populations and are associated with indoor cooking with wood on open, unvented stoves. These metabolite concentrations were also associated with the presence of advanced esophageal dysplasia. Our findings underline the importance of assessing alternative cooking conditions to reduce PAH exposure in this population.